Stabilization of radiation intensity at an electron-based THz radiation facility - Ko, Jun Ho; Ko, In Soo; Jung, Seong Hoon; Park, Jaehun; Kang, Heung Sik (Journal of the Korean Physical Society, 2018)
The femtosecond (fs) terahertz (THz) beamline of Pohang Accelerator Laboratory (PAL) is providing a THz radiation with the pulse energy of 7 μJ by means of coherent transition radiation (CTR) from a 65-MeV electron beam. The fs-THz beamline is dedicated to the user service operation for which we need to provide a stable radiation for beamline experiments. For this purpose, we have improved electron bunch length measurement and an RF phase feedback system for stabilizing the THz radiation intensity.